Karma Doll - Ames, Jonathan (The Doll series, 2025)
"After narrowly escaping with his life at the hands of a murderous Hollywood pimp, detective Happy Doll, bullet-ridden but healing, has landed on a remote Mexican beach. In a humble shack and with his dog for company, Doll settles into a peaceful idyll of Buddhist study. But then trouble, as it always does, comes to paradise. Doll is the witness to a murder for which he is framed, and now, with an expired passport and the Mexican authorities on his tail, he must sneak across the border back to L.A. by any means necessary, with the goal of bringing the true murderer to justice. But it's not just trouble that expels Doll from paradise! His dark past reaches for him, like a hand from the grave, old enemies want him dead, including the Jalisco Cartel, and Doll, a reluctant instrument of mayhem, yearns to end this cycle of violence and tip the karmic scales in his favor. But how can he do this without getting blood on his hands? Karma Doll marks the third installment in a madcap, bloody, and impossibly fun series, bringing us back in the good company of Happy Doll: a beloved, introverted anti-hero who has taken more hits to the head than a linebacker, yet still always manages to come out on top." --